Optimalisasi Transpormasi Digital Melalui Pengelolaan Metadata yang Efektif - Muhammad Febry Choir; Muhammad Irwan Padli Nasution (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
Digital transformation is a strategic step taken by organizations to improve efficiency, competitiveness, and service quality through the use of digital technology. One of the key elements in supporting the success of digital transformation is effective metadata management. Metadata, as data about data, plays an important role in improving the accessibility, interoperability, and integrity of digital information. This article discusses how systematic and standardized metadata management can optimize the digitalization process, accelerate information retrieval, and support data-based decision making. With a literature study approach and best practice analysis, this article outlines a metadata management strategy that can be integrated into the digital transformation framework. The results of the study show that the implementation of appropriate metadata policies, the use of supporting technology, and increasing data literacy in the organizational environment are determining factors in creating a resilient and adaptive digital ecosystem.